Investment Commitments in Latin America and the Caribbean Increased in 2007 - Izaguirre, Ada Karina; Jett, Alexander Nicholas (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in Latin America and the Caribbean grew by 28 percent to US$38.3 billion in 2007, according to just-released data from the private participation in infrastructure project database. The region accounted for 24 percent of the year's total investment commitments in developing countries. Despite having grown for four consecutive years, investment commitments remained well below the region's peak levels reached in 1997-98. Investment in 2007 was just 44 percent of the peak in 1998. Previously implemented projects largely drove the 2007 investment. Projects reaching financial or contractual closure in 1990-2006 attracted US$22.3 billion, while the 46 new projects implemented in 2007 accounted for US$16 billion. Investment in physical assets amounted to US$32.5 billion. Indeed, if only investment in physical assets were counted-that is, excluding payments to the government (such as divestiture revenues and spectrum or concession fees) investment in 2007 would be just 22 percent below the peak level of 1998.